Defence Anaesthesia transition from the Tri-Service Anaesthetic Apparatus to the Diamedica Portable Anaesthesia Machine 02. Issue 5 (October 2019) - Pearson, Jonathan David; Maund, A; Jones, CP; Coley, E; Frazer, S; Connor, D
Abstract : Defence Anaesthesia is changing its draw-over anaesthetic capability from the Tri-Service Anaesthetic Apparatus (TSAA) to the Diamedica Portable Anaesthesia Machine 02 (DPA02). The DPA02 will provide a portable, robust, lightweight and simple method for delivering draw-over volatile anaesthesia with the option of positive pressure ventilation through manual or mechanical operation for paediatric and adult patients. The UK Defence Medical Services uses a modified configuration of the DPA02; this paper seeks to explain the rationale for the differing configurations and illustrates alternative assemblies to support integration with other Defence Anaesthesia equipment. High-fidelity simulation training using the DPA02 will continue to be delivered on the Defence Anaesthesia Simulation Course (DASC). Conformité Européenne accreditation of DPA02 supports future UK live patient training in centres of excellence supervised by subject matter experts; this was not possible with the TSAA. This article is intended to be a key reference for all members of the Defence Anaesthesia team. Alongside other resources, it will be given as precourse learning prior to attending the DASC and the Military Operational Surgical Training. This article will also be issued with all Defence DPA02 units, supporting ease of access for review during future clinical exercises (including validation), prior to supervised live training and on operational deployments.